Relawan, Donasi dan Kunjungan di Desa Batok Untuk Mempromosikan Hidup Sehat - Pierre Mauritz Sundah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Health must be fought for by everyone because health is a primary need for every individual to be able to live productively. Healthy conditions will make a person able to achieve a high-quality life. Through this program, it is hoped that it can help students to increase social awareness and provide social assistance to the community at Desa Batok, Tenjo. It requires awareness, understanding, and proper insight to implement a healthy lifestyle and take preventive steps against health problems. This program is carried out from March to May 2022 and consists of three forms of events which are Open Volunteer, Open Donation, and Visitation. Volunteers will be provided with a material enrichment program that will mainly discuss health issues and the application of a healthy lifestyle that will be used to educate the society during pandemics. Donation will be used to give health necessities and medical equipment and medicines for the people at Desa Batok. Visitation are held volunteers share knowledge to local communities and also educate them about healthful living today. This program also did a disinfectant fogging for several public areas in Desa Batok.